Pengaruh Produk, Harga, Tempat, dan Promosi Terhadap Keputusan Pembelian Konsumen di Bahrul Maghfiroh Mart Kota Malang - Ninda Rachmawati,; Anudiyan Amir Mas'ud, (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2022)
This study aims to examine and analyze:1 the influence of simultaneous marketing mix on purchasing decisions at Bahrul Maghfiroh Mart Kota Malang, 2 the effect of the product partially on the Purchase Decision at Bahrul Maghfiroh Mart Kota Malang, 3 the effect of price partially on the Purchase Decision on Bahrul Maghfiroh Mart Kota Malang. 4 the influence of place partially on the purchase decision at Bahrul Maghfiroh Mart Kota Malang. And 5 the partial effect of promotion on purchasing decisions at Bahrul Maghfiroh Mart Kota Malang. This study uses a survey method and the data collection process is carried out by distributing questionnaires to consumers. The population in this study are product buyers at Bahrul Maghfiroh Mart Kota Malang which is not known for certain. The sampling technique used purposive sampling, with a total sample of 75 respondents. The data analysis technique used multiple linear regression. The results showed that: 1 product, price, place, promotion simultaneously had a Negative and not significant effect on purchasing decisions. 2 the product partially has a positive and significant effect on purchasing decisions. 3 price partially has a positive and significant effect on Purchase Decisions 4 Place partially has a Negative and Not significant effect on Purchase Decisions 5 Promotion partially has positive and significant effect on Purchase Decisions.